1997
DOI: 10.1172/jci119207
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 6 causes growth impairment in transgenic mice through a decrease in insulin-like growth factor-I. A model for stunted growth in children with chronic inflammation.

Abstract: Stunted growth is a major complication of chronic inflammation and recurrent infections in children. Systemic juvenile rheumatoid arthritis is a chronic inflammatory disorder characterized by markedly elevated circulating levels of IL-6 and stunted growth. In this study we found that NSE/hIL-6 transgenic mouse lines expressing high levels of circulating IL-6 since early after birth presented a reduced growth rate that led to mice 50-70% the size of nontransgenic littermates. Administration of a monoclonal anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
342
1
11

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 473 publications
(380 citation statements)
references
References 40 publications
(50 reference statements)
22
342
1
11
Order By: Relevance
“…These observations demonstrate that chronic overproduction of IL-6 can cause a growth defect, and that this growth defect is associated with abnormalities of the IGF-1 system similar to those found in patients. In further support of the relationship between IL-6 and the IGF-1 system, in patients with systemic JIA, circulating levels of IL-6 are inversely correlated with levels of IGF-1 and IGFBP-3 (46,49).…”
Section: Role Of Il-6 In Systemic Jiamentioning
confidence: 81%
See 1 more Smart Citation
“…These observations demonstrate that chronic overproduction of IL-6 can cause a growth defect, and that this growth defect is associated with abnormalities of the IGF-1 system similar to those found in patients. In further support of the relationship between IL-6 and the IGF-1 system, in patients with systemic JIA, circulating levels of IL-6 are inversely correlated with levels of IGF-1 and IGFBP-3 (46,49).…”
Section: Role Of Il-6 In Systemic Jiamentioning
confidence: 81%
“…IL-6-transgenic mice with high circulating levels of IL-6 since birth show a decreased rate of growth, attaining 50-60% of the size of their wild-type littermates as adults (46). Similar to patients with systemic JIA (47,48), IL-6-transgenic mice have normal growth hormone production but low levels of insulin-like growth factor 1 (IGF-1) and IGF binding protein 3 (IGFBP-3) (46,49). These observations demonstrate that chronic overproduction of IL-6 can cause a growth defect, and that this growth defect is associated with abnormalities of the IGF-1 system similar to those found in patients.…”
Section: Role Of Il-6 In Systemic Jiamentioning
confidence: 99%
“…However, inflammation per se may also modulate plasma IGF-I levels. First, the proinflammatory cytokines IL-1b, IL-6 and TNF-a inhibit expression of the IGF-I gene (44,45), and low circulating IGF-I concentration may be caused by a direct effect of cytokines in the liver. This effect may involve suppression of cytokine signaling inhibition of GH signaling by proinflammatory cytokines (46,47).…”
Section: Discussionmentioning
confidence: 99%
“…In transgenic mice, overexpressing IL-6 severely impaired growth associated with very low serum IGF-I concentrations was shown (16). We showed that in inflammatory bowel diseases in relapse, serum IL-6 and IGFBP-2 were increased and positively correlated (17).…”
Section: Introductionmentioning
confidence: 98%